Transforming Books: Paper, Metamedia and Digitisation: White Magic: The Age of Paper*, Lothar Müller, Cambridge: Polity, 2015, ISBN: 978-0-7456-7253-3. (15th November 2016) - Lockett, Andrew
This review asks what a history of paper and a study of metamedia tell us about the paper v. digital debate reported in the media taking place within the trade book publishing industry just as figures reported in 2016 show that eBook sales are slowing and print is showing a very tiny recovery. Müller's book shows how paper was the 'old' digital, transformative, mythical even, whereas the rise of metamedial literature in Starre's book reflected a rise in interest in the material aspects of book objects (and control of) by authors as the vanilla incarnation of digital – the eBook – disappointed. As the mixed ecology of print and digital looks set to continue as both books argue, this review asks whether industry concentration and consolidation is becoming the lead story not ever increasing levels of digital activity.